Microbially-induced sedimentary structures (MISS) as record of storm action in supratidal modern estuarine setting - Cuadraro, Diana (2013)
One of the aims of tidal sedimentology in recent years is to ﬁnd signatures in the stratigraphic record that help in recognizing basic ancient tidal processes. The present study was carried out on the supratidal zone of the middle Bahía Blanca estuary which is colonized by extensive microbial mats.The purpose of the study was to relate the tidal and wave energy with the microbially-induced sedimentary structures (MISS) present in the tidal ﬂat.Theenergy reaching the area was quantiﬁed by tidal and wave records, while MISS were simultaneously recognized and described after a strong storm event. The MISS and the microsequences of sediments in vertical crosssections of the tidal ﬂat were considered as tidal signatures over a supratidal zone, when high-tide in severe energy conditions can reach the zone. This paper contributes to the understanding of physical sedimentary parameters that control the modiﬁcation of microbial structures in modern siliciclastic regimes and that, in turn, can aid in the reconstruction of ancient hydraulic settings.